Strategi Adaptasi SMA N 1 Payakumbuh terhadap Sistem Zonasi - Salsabila Dinda Ramadani; Nurlizawati Nurlizawati; AB Sarca Putera (Naradidik: Journal of Education and Pedagogy, 2022)
This study discusses the adaptation strategy of SMA N 1 Payakumbuh with zoning and knowing the changes that have occurred after the zoning system at SMA N 1 Payakumbuh. This study uses a descriptive approach with qualitative research methods. The data collection techniques that the researchers used were observation, interviews, and documentation. The data analysis used in this study used the Miles and Huberman interactive model through several activity procedures including data reduction, data presentation, and drawing conclusions or levers. The results showed: first, changes in student input which were relatively heterogeneous after the implementation of the zoning system led to changes in learning patterns; second, the lack of public understanding of zoning; third, the strategy carried out by schools at SMAN 1 Payakumbuh in adjusting to the zoning is to make extracurricular activities at this time and fourth, inculcating values, increasing motivation by subject teachers and counseling teachers (Counseling Counseling).